(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2024)
This study investigates communication barriers faced by Tanzanian immigrants serving prison terms in Ghana for various offences. Given the role of communication in inmates’ daily lives, including various processes and procedures within the prison yards, the study seeks to examine strategies employed by such inmates to meet their social/communicative needs within the prison environs. The study is carried out against the backdrop of some East African migrants encountering communication barriers in Ghana. The main objective is to investigate the effect of communication barriers on Tanzanian inmates at Nsawam Prisons and the linguistic support system in place within the prison yards for such inmates. The study also looks at the coping strategies to overcome such communicative barriers and the long-term negative and positive effects of the language barrier on their linguistic abilities. Data were collected by two research assistants with funding support from the Andrew Mellon Foundation through the administration of questionnaires and interview sessions with five Tanzanian inmates. The findings of the study indicate that in addition to the use of similar coping strategies that are used by other East African migrants, resident in Ghana, such as gestures and the seeking of assistance for interpretation, Tanzanian inmates in Nsawam Prisons ultimately learn a Ghanaian language because they see the acquisition of a Ghanaian language as an effective solution to the challenges of language barriers at the Nsawam Prisons. It was also noted that although gender differences played a role in the linguistic choices of these inmates, individual preferences for negotiating linguistic barriers were paramount.